REVITALISASI GENERASI MUDA GEN Z DALAM MEMOTIVASI BAKAT DAN MINAT MENEKUNI PEWAYANGAN BALI DI SMKN 3 SUKAWATI, GIANYAR - I Ketut Muada; Nyoman Astawan; I Nyoman Sadwika (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Balinese puppetry is an intangible cultural heritage containing philosophical, aesthetic, moral, and spiritual values ​​important to society. However, technological advancements and changing entertainment preferences have led to a decline in interest among the younger generation, particularly Gen Z, in puppetry. Gen Z is more interested in digital content, thus limiting their exposure to traditional arts. This Community Service (PKM) activity responds to this situation through a revitalization program that combines a practical approach, creative workshops, digital content training, and mentoring by young puppeteers to increase participant motivation and interest. The activity methods include explanations of the history and philosophy of puppetry, demonstrations of puppetry techniques, character play practice, cultural content creation, and final project mentoring. The results of the activity indicate an increase in participants' knowledge, motivation, basic puppetry skills, and digital participation. This program has a sustainable impact through the formation of a student community that cares about puppetry and increased exposure to puppetry in digital media.